Effectiveness of Subliminal Stimuli in Lie Detection: Use of Physical Countermeasures - Sharma, Mandeep; Yadava, Amrita; Sharma, Nov Rattan (Defence Life Science Journal, 2018)
The objective of the present investigation was to study the effectiveness of subliminal stimuli in reducing the probability of use of countermeasures during polygraph was considered. Further, use of countermeasures (physical) would be more for supraliminal stimuli as compared to subliminal stimuli. Purposive total samples of 79 adults with (age range between 20-28 years) were selected for the present study. Windows Based Computerised Lie Detector (CLD-118) and Aversion Therapy Instrument (MBT-498) were used in present study. For analyses of the data, Friedman Test (non-parametric) followed by Wilcoxon Signed-Rank Test (non-parametric), were applied. In the present investigation the effectiveness of subliminal stimuli in deterring the execution of countermeasures was studied, revealed that subliminal stimuli acted as a deterrent to physical countermeasures. The present findings indicate that subliminal stimuli can be used as a deterrent to countermeasures (Physical) in Lie Detection.